A comparative study of morbidity and symptom severity among double-J stented patients with and without tamsulosin administration - Kucherlapati, Abhiram; Ravi, Dinesh K.; Jain, Udit; Dayaphule, Sreedhar; Theja, Bathalapalli R.; Jagirdar , Faisal (International Journal of Research in Medical Sciences, 2024)
Background: The insertion of a double-J (DJ) stent is considered a routine and necessary urological procedure. The symptoms produced by the stent are predominantly irritative in nature and the use of alpha blockers like tamsulosin have shown considerable in treating the stent associated symptom. Aim of the study was to assess tamsulosin's impact on ureteral stent-associated morbidity. Methods: A comparative cross-sectional study. All the patients with ureteric calculi admitted in the department of urology, Narayana Hospital, Nellore, Andhra Pradesh. Results: A total of 80 patients who met the inclusion criteria, were divided into two groups. Group A receiving placebo and group B receiving tamsulosin 0.4 mg. Among the study population, there was statistically significant difference between the means of parameters between the groups during the stent removal. The means of group B were significantly lower than the means of group A which shows that tamsulosin is very effective in managing the pain and also the stent related morbidity. Conclusions: Tamsulosin is very effective in managing the pain and also the stent related morbidity, which was measured by international prostate symptom score (IPSS) score – both obstructive and irritative. The quality of life was suggestively better in tamsulosin group.